Detection of Lactoferrin and Iron in Seminal Plasma and Their Possible Relation to Semen Parameters and Infertility in Varicocele: A Cross-sectional Study - Ali Mohamed Mahran; Marilyn Sameh Abd-Almalak; Fatma Mohammed Helbawi; Marwa Mohammad Mekkawy (Journal of Human Reproductive Sciences)
Background: Male infertility emerges as an important cause during the evaluation of infertile couples. Varicocele is a well-known cause of male infertility. The role of seminal lactoferrin, an iron-binding glycoprotein, in male fertility is unclear and needs further investigation. Recently, it has been linked to some sperm abnormalities and subfertility. Aim: This study aims to detect seminal lactoferrin levels in infertile men with varicocele and their relation to semen parameters and fertility status. We investigated a possible link between seminal lactoferrin and iron. Settings and Design: A cross-sectional study was conducted through the outpatient clinic. Materials and Methods: Seventy-five individuals were included in 3 groups (33 infertile men with varicocele, 25 infertile men without varicocele and 17 fertile participants without varicocele). Conventional semen analysis was conducted, and seminal plasma was obtained in all groups to detect lactoferrin and iron levels. Statistical Analysis Used: Statistical analysis was performed by SPSS version 24. Results: In infertile men with varicocele, seminal lactoferrin (155.92 ± 8.4 ng/ml, P = 0.296) and iron levels (260.71 ± 38.3 μg/dl, P = 0.409) were not significantly different from other groups. There was a positive correlation between seminal lactoferrin, iron levels and sperm concentrations and counts. Seminal iron and lactoferrin were significant independent predictors of sperm concentration. A negative correlation was reported between seminal lactoferrin levels and age. Lactoferrin in seminal plasma was not correlated with seminal iron. Conclusion: Infertile men with varicocele have seminal lactoferrin levels comparable to other infertile men and possibly fertile individuals. Iron concentrations are not linked to lactoferrin levels in seminal plasma.